Interplay between microtubule interactome, myonuclei mechanotransduction, and positioning in myopathies - Léa Castellano; Damien Caillol; Nathalie Streichenberger; Vincent Gache (Nucleus, 2025)
Myofibers are the building block of skeletal muscle cells providing its capacity to contract and produce movement. The microtubule (MT) network sustains myofiber formation and its spatial organization is remodel during myofiber formation. This muscle-related MT network with specific partners, actively drive myonuclei localization in myofiber. In pathological conditions, myonuclei and MT patterning are affected and contribute to skeletal muscle mis-functionality. In this review, we classified myopathies depending on myonuclei positioning within myofibers and reported that 72% of myopathies exhibit myonuclei positioning alterations. We explored how this impairment can be analyzed according to muscle disease development, MT alterations and association with various partners. We highlighted how MT modifications impact muscle-specific mechanotransduction status and myofiber functional integrity. We then reported genes involved in myonuclei shape and positioning maintenance. Finally, we discussed technical contribution advances in the field to improve knowledge on muscle physiology and its challenges in disease context.